Of course scientists can communicate - Radford, Tim (Nature (London), 2011)
Another was the industrial chemist, poet and writer Primo Levi, who when I tried to ask him about the Two Cultures debate - the apparent divide between the humanities and sciences - gently reminded me that Dante Alighieri (himself the subject of at least one paper in Nature), was a member of the Florentine guild of physicians and apothecaries. [...] a third was the Czech poet and dissident Miroslav Holub, who wrote his occasional Guardian column in English, and asked that at the end of each I describe him as the author of Immunology of Nude Mice (1989). [...] their fame became inseparable from their gift for words.